British-Soviet Cooperation in Trade and Economic Sphere in the Second Part of 1980 - Машевський О.; Садикова В. (Видавничо-поліграфічний центр "Київський університет", 2014)
This article is devoted to the problem of trade and economic relations between Great Britain and the Soviet Union in the second part of 1980. Deepen British-soviet economic relations by strengthening personal contacts of M. Thatcher and M. Gorbachev, concluding a number of mutual advantageous agreements and realization bilateral cultural events, including "Days of Great Britain" in the USSR in Kiev are analysed.

У статті розглядаються особливості торговельно-економічних відносин Великої Британії та Радянського Союзу в другій половині 1980-х рр. Проаналізовано поглиблення британсько-радянських економічних зв'язків шляхом зміцнення особистісних контактів М. Тетчер та М. Горбачова, укладання низки взаємовигідних угод та проведення двосторонніх культурних заходів, зокрема "Днів Великої Британії" в СРСР у м. Києві.
Британсько-радянське співробітництво в торговельно-економічній галузі в другій половині 1980-х рр.
Keywords: Great Britain; USSR; trade and economic cooperation; M. Thatcher; M. Gorbachev; Велика Британія; СРСР; торговельно-економічне співробітництво; М. Тетчер; М. Горбачов